Margin trading bans in experimental asset markets - Sascha Füllbrunn; Tibor Neugebauer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
In financial markets, professional traders leverage their trades because it allows to trade larger positions with less margin. Violating margin requirements, however, triggers a margin call and open positions are automatically covered until requirements are met again. What impact does margin trading have on the price process and on liquidity in financial asset markets? Since empirical evidence is mixed, we consider this question using experimental asset markets. Starting from an empirically relevant situation where margin purchasing and short selling is permitted, we ban margin purchases and/or short sales using a 2x2 factorial design to a allow for a comparative static analysis. Our results indicate that a ban on margin purchases fosters efficient pricing by narrowing price deviations from fundamental value accompanied with lower volatility and a smaller bid-ask-spread. A ban on short sales, however, tends to distort efficient pricing by widening price deviations accompanied with higher volatility and a large spread.
Keywords: C92; D70; G12; 330; Leverage; asset Market; price bubble; experimental finance; Wertpapierhandel; Regulierung; Wertpapierspekulation; Schulden; Börsenkurs; Bubbles; Börsenspiel; Leerverkauf